Four Ps of Creativity and Behavioural Intentions in Creative Tourism: The Mediating Role of Experience Quality - Mohd Fahmi, Yahaya; Ahmad Azmi, M. Ariffin (University of Rijeka, Faculty of Tourism and Hospitality Management, Croatia, 2025)
Purpose: This study explores how the dimensions of creativity—specifically person, process, product, and press—affect tourists’ behavioural intentions. Additionally, this study examines how experience quality mediates these relationships. Methodology/Design/Approach: This study used a survey instrument to gather data from 500 creative tourists in Malaysia. To test the structural model, Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed. Findings: The result highlights the influence of the four Ps of creativity on the behavioural intentions of tourists within the creative tourism sector. The study also investigates how experience quality affects these relationships Originality of the research: The novelty of this study lies in the integration of the four Ps of creativity and experience quality into a single model for predicting the future behaviour of creative tourists.